Do healthcare challenges influence patient satisfaction in foreign countries? Evidence from international students in China - Bano, Abida (Journal of International Students, 2026)
This study investigated healthcare challenges faced by international students in China and their impact on satisfaction levels. A mixed-methods approach, including interviews, was used to identify barriers such as language difficulties, limited insurance, mental health issues, and healthcare utilization patterns. Guided by Andersen’s behavioral model and Berry’s acculturation theory, the findings reveal that inadequate health insurance significantly limits access and satisfaction, whereas language and mental health challenges worsen the situation. Statistical analyses, including multiple regression and structural equation modeling, confirmed that accessibility is positively correlated with patient satisfaction. This study highlights the need for early identification and intervention by universities and healthcare providers through expanded insurance, culturally appropriate mental healthcare, and improved communication. By addressing these barriers, this research enhances the understanding of international students’ healthcare experiences and provides policy recommendations to promote a more supportive healthcare environment for this population in China.